Polymorphous billiard with chaotic beams dynamics - Naydenov, S.V.; Maslovsky, Yu.N.; Yanovsky, V.V. (Functional Materials, 2006)
A new type of billiard is introduced - the one with chaotic beams dynamics. The dynamics of dumbbell-like polymorphous billiards family is studied. The chaotic behaviour of the beams and their uniform stationary distribution are proved. The chaotic properties found let one use polymorphous billiard in physical applications. Предложен новый тип биллиарда с хаотической динамикой лучей. Изучена динамика семейства полиморфных биллиардов в форме гантели. Доказано хаотическое поведение лучей и их равномерное стационарное распределение. Обнаруженные хаотические свойства позволяют использовать полиморфный биллиард в различных физических приложениях. Запропоновано новий тип більярду з хаотичною динамікою променів. Вивчено динаміку ряду поліморфних більярдів у формі гантелі. Доведено хаотичну поведінку променів та рівномірність їхнього стаціонарного розподілу. Винайдені хаотичні властивості дозволяють використовувати поліморфний більярд у різних фізичних системах.